LOGOTYPE AND EMBLEM AS CONSTITUENTS OF CORPORATE IDENTITY OF EDUCATIONAL ESTABLISHMENTS OF UKRAINE - Васильєва, О. С.; Пашкевич, К. Л.; Васильєва, І. В.; Гричанюк, О. В.; Калун, О. Ю. (Art and Design, 2021)
Purpose. The purpose of this article is to identify the characteristic design features of the corporate identity elements used in school uniforms in Ukraine, which have developed under the influence of national and cultural traditions. The objects of analysis were samples of emblems and logos of Ukrainian educational schools, which are visual symbols of the school and part of the design of a school uniform. Methodology. Methodological basis of research is complex approach, methods of visually analysis of research object, systematization of varieties of emblems and logotypes of educational school of Ukraine. Results. The most characteristic artistically-composition decisions of emblems of educational school of Ukraine are analysed and distinguished: their basic types, characteristic symbolics and colour decisions. The typology of the graphical elements used in emblems, as means of communication, is offered by semantic value for producing an image and corporate identity of educational school. The basic types of the logotypes used in the design of school uniform suit of school of Ukraine. Scientific novelty.The imagery of emblems of educational establishments of Ukraine are systematized by their semantic value. Characteristic variations of combination of clip arts and colour combinations are certain in the brandname symbolics of educational establishments of Ukraine. The basic types of the logotypes used in the design of school uniform suit in Ukraine. Practical significance. Classification of graphical elements of emblems of educational establishments of Ukraine is worked out allowed to generalize the artistically-composition features of their brandname style and feature of their use in a design school service dress for visual репрезентации and translation of values and basic descriptions of educational establishment. Research materials can be used for development of brandname style and design modern school uniform